Legal Protection on E-Commerce Transactions: Problems and Challenges in Global Business - Santoso, Vira Aprillia (Faculty of Law Universitas Negeri Semarang, 2021)
Electronic commerce or so-called E-Commerce is a borderless market that can transcend all borders, such as time differences, language differences, currency differences and regulatory differences. E-Commerce is very popular with today's society because of the many conveniences that exist in it, because many users of the problem also increasingly colorful, the country is already set through the Consumer Protection Act. Unlimited E-Commerce transactions that transcend regional differences in the event of a dispute are often resolved through Alternative Dispute Resolution (ADR) in which there are various forms such as negotiation, mediation, conciliation, consultation, expert judgment and arbitration. ADR is a non litigation path because if solved by a litigation path it will definitely take longer.